Protein-Directed Immobilization of Phosphocholine Ligands on a Gold Surface for Multivalent C-Reactive Protein Binding - Kim, Eunjoo; Lee, Se Geun; Kim, Hyun-Chul; Lee, Sung Jun; Baek, Chul Su; Jeong, Sang Won (Current Topics in Medicinal Chemistry, 2013)
The preparation of a synthetic receptor for multivalent protein binding by a directed immobilization of bifunctional ligands was demonstrated using pentameric C-reactive protein (CRP) and a thiolated phosphocholine-containing ligand on a gold surface. CRP consisting of five identical, noncovalently linked subunits and having five phosphocholinebinding sites on the same face was complexed with 12-mercaptododecylphosphocholine. The complexes were reacted with a gold surface, which was blocked with BSA or 2-mercaptoethanol to avoid non-specific binding. CRP binding to the molecularly imprinted monolayer was investigated by surface plasmon resonance, exhibiting high sensitivity with a detection limit as low as 1 pM (0.12 ng/mL) and binding affinity (KA 10-7-10-9 M-1) comparable to that of immobilized anti- CRP.
Keywords: surface plasmon resonance